2018
DOI: 10.5511/plantbiotechnology.18.0412a
|View full text |Cite
|
Sign up to set email alerts
|

Control of plant growth and development by overexpressing <i>MAP3K17</i>, an ABA-inducible MAP3K, in <i>Arabidopsis</i>

Abstract: Abscisic acid (ABA) plays an important role in plant growth, development, and stress responses. ABA regulates many aspects of plant growth and development, including seed maturation, dormancy, germination, the transition from vegetative to reproductive growth, leaf senescence and responses to environmental stresses, such as drought, high salinity and cold. It is also known that mitogen-activated protein kinase (MAPK) cascades function in ABA signaling. Recently, we and another group have identified the ABA-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Here, the discrepancy of H 2 O 2 may result from different defensive mechanisms which are triggered by herbivores and pathogens in plants. ABA treatment activated MAPKKK17/18, which participated in ABA signaling through the MKK3-MPK1/2/7/14 cascade [35,54,55]. In addition to the MKK3–MPK7 cascade response to H 2 O 2 in Arabidopsis [34], OsMKK3 interacted with OsMPK7 in response to H 2 O 2 and positively regulated resistance to X. oryzae in rice [37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, the discrepancy of H 2 O 2 may result from different defensive mechanisms which are triggered by herbivores and pathogens in plants. ABA treatment activated MAPKKK17/18, which participated in ABA signaling through the MKK3-MPK1/2/7/14 cascade [35,54,55]. In addition to the MKK3–MPK7 cascade response to H 2 O 2 in Arabidopsis [34], OsMKK3 interacted with OsMPK7 in response to H 2 O 2 and positively regulated resistance to X. oryzae in rice [37].…”
Section: Discussionmentioning
confidence: 99%
“…Such growth retardation in mutants is in line with previous reports. For example, MKK3 negatively influenced plant growth which indicated that MKK3 mediated overexpression AtMAPKKK17/18 attributing impaired Arabidopsis growth such as decreased plant weight and rosette diameter [54,55]. Meanwhile, Enders indicated that the MKK3–MPK1 cascade pathway has a negative regulation on auxin-dependent cell growth in Arabidopsis [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of gene changes with environmental stress and pathogen infection. It is previously shown that Arabidopsis MAPK1/2/7/14 are induced by ABA [30,31]. Some of watermelon ClMAPKs (ClMAPK1, ClMAPK3, ClMAPK4-1, ClMAPK4-2, ClMAPK6, ClMAPK7, ClMAPK9-1, ClMAPK9-2, ClMAPK13, ClMAPK16, ClMAPK19, ClMAPK20-1, ClMAPK20-2) can respond to drought stress [37].…”
Section: Plos Onementioning
confidence: 99%
“…For instance, Arabidopsis contains 80 MAPKKKs, 10 MAPKKs and 20 MAPKs [24,25] which are involved in the regulation of low temperature, drought, disease resistance and other processes [12,[26][27][28][29]. The latest studies have shown that MAPKKK17/18-MKK3-MAPK1/2/7/14 participates in the signal transduction induced by abscisic acid (ABA) [30,31]. MAPKKK3/5-MKK4/5-MAPK3/6 is involved in a variety of pathways in plant defense pathogens, including the synthesis of ethylene and phytoalexin, the thioglycoside biosynthetic pathway and stomatal immunization [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%